Individual patient data meta-analysis of acupuncture for chronic pain: protocol of the Acupuncture Trialists' Collaboration - Vickers, Andrew J.; Cronin, Angel M.; Maschino, Alexandra C.; Lewith, George; Macpherson, Hugh; Victor, Norbert; Sherman, Karen J.; Witt, Claudia; Linde, Klaus (Trials, 2010)
The purpose of clinical trials of acupuncture is to help clinicians and patients make decisions about treatment. Yet this is not straightforward: some trials report acupuncture to be superior to sham (placebo) acupuncture while others show evidence that acupuncture is superior to usual care but not sham, and still others conclude that acupuncture is no better than usual care. Meta-analyses of these trials tend to come to somewhat indeterminate conclusions. This appears to be because, until recently, acupuncture research was dominated by small trials of questionable quality. The Acupuncture Trialists' Collaboration, a group of trialists, statisticians and other researchers, was established to synthesize patient-level data from several recently published large, high-quality trials.
The Acupuncture Trialists' Collaboration: Claire Allen, Mac Beckner, Brian Berman, Benno Brinkhaus, Remy Coeytaux, Angel M. Cronin, Hans-Christoph Diener, Heinz G. Endres, Nadine Foster, Juan Antonio Guerra de Hoyos, Michael Haake, Richard Hammerschlag, Dominik Irnich, Wayne B. Jonas, Kai Kronfeld, Lixing Lao, George Lewith, Klaus Linde, Alexandra Maschino, Dieter Melchart, Albrecht Molsberger, Hugh MacPherson, Eric Manheimer, Karen J. Sherman, Hans Trampisch, Jorge Vas, Andrew J. Vickers (collaboration chair), Norbert Victor, Peter White, Stefan N. Willich, Claudia M. Witt
Gesehen am 05.09.2023